Modernidade, paisagem e fotografia: o bairro de Pinheiros em perspectiva (1908-1969) - Richter, Larissa [UNIFESP] (2019)
This research’s goal is to problematize and to understand the landscape changes that happened in the neighborhood of Pinheiros during the modernizing process that the city of São Paulo went through (while it became a metropolis). The main sources are photographic documents that were produced regarding Pinheiros since the beginning of the 20th century until the late 1960’s. The public constructions regarding Pinheiros’s river straightening, wide avenues making, streets asphalting and waters channeling are landscape changes in that neighborhood that ended ancient activities typical of that region. The end of such practices affected how the habitants related to and remembered that space while the city became a huge metropolis. The photographies that are analyzed, besides seen as a visual reference, are also seen as a modern vehicle that worked as propaganda for different modernizing ideals that were common during the 20th century.